Empowering the Community Economy through the Enpowerment and Development of Sharia-Based Cooperatives in East Bandung - Sakuroh, Lilis (Yayasan Pendidikan Belajar Berdikari, 2025)
Sharia-based cooperatives represent a strategic instrument in strengthening the ummah's economy and fostering community economic independence. This study aims to analyze the role of sharia-based cooperatives in empowering the community economy, particularly in the context of social justice, equitable welfare, and financial inclusion. A qualitative approach is employed, incorporating literature review and field data from several Islamic cooperatives in West Bandung. The results indicate that sharia cooperatives serve as an alternative solution for small and medium communities in accessing financing and enhancing business productivity. However, challenges persist, including limited capital, low sharia literacy, and suboptimal cooperative management. Key recommendations include strengthening empowerment policies, continuous coaching, and integrating Islamic cooperatives into the digital economic ecosystem